Space of ω-Periodic Limit Functions and Its Applications to an Abstract Cauchy Problem. (12th March 2015) - Xie, Rui; Zhang, Chuanyi
Abstract : We introduce a new space consisting of what we callω -periodic limit functions. We investigate some properties of the new function space. In particular, we study inclusion relations among asymptotically periodic type function spaces. Finally, we apply theω -periodic limit functions to investigate the existence and uniqueness of asymptoticallyω -periodic mild solutions of an abstract Cauchy problem.